Databook of surface modification additives - Wypych, George (ChemTec Publishing, 2018)
Databook of Surface Modification Additives contains data on 7 groups of additives, including anti-scratch and mar-preventing additives, gloss enhancement and surface matting additives, additives for formation of tack-free surface and tackifiers, and stain inhibiting additives. The information on each adhesion promoter is divided into five sections, including General Information, Physical Properties, Health and Safety, Ecological Properties and Use and Performance. This databook will be an extremely useful source of data for engineers, researchers and technicians interested in using additives to modify and improve the surface properties of materials.